Batch-Size Independent Regret Bounds for Combinatorial Semi-Bandits with Probabilistically Triggered Arms or Independent Arms - Liu, Xutong; Zuo, Jinhang; Wang, Siwei; Joe-Wong, Carlee; Lui, John C.S.; Chen, Wei (Proceedings of the 36th Conference on Neural Information Processing Systems (NeurIPS), 2022)
In this paper, we study the combinatorial semi-bandits (CMAB) and focus on reducing the dependency of the batch-size K in the regret bound, where K is the total number of arms that can be pulled or triggered in each round. First, for the setting of CMAB with probabilistically triggered arms (CMAB-T), we discover a novel (directional) triggering probability and variance modulated (TPVM) condition that can replace the previously-used smoothness condition for various applications, such as cascading bandits, online network exploration and online influence maximization. Under this new condition, we propose a BCUCB-T algorithm with variance-aware confidence intervals and conduct regret analysis which reduces the O(K) factor to O(log K) or O(log^2 K) in the regret bound, significantly improving the regret bounds for the above applications. Second, for the setting of non-triggering CMAB with independent arms, we propose a SESCB algorithm which leverages on the non-triggering version of the TPVM condition and completely removes the dependency on K in the leading regret. As a valuable by-product, the regret analysis used in this paper can improve several existing results by a factor of O(log K). Finally, experimental evaluations show our superior performance compared with benchmark algorithms in different applications.